ANALISIS DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI AKREDITASI BERBASIS WEB PADA BADAN AKREDITASI PROVINSI PENDIDIKAN ANAK USIA DINI DAN PENDIDIKAN NON FORMAL (BAP PAUD DAN PNF) - Suwarto, Suwarto; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2017)
Since acreditation program for Early Childhood Education Institution and Nonformal Education Institution wasexecuted manually. The processess require much staffs to accept accreditation proposals, check them using manualinstruments as well as reporting the checking result and reporting the riil condition of the institution. These set ofactivities are sometimes troubled by â€œself-tired conditionâ€ and the possibility of â€œdata lostâ€. If these occured willcause unobjectivity of accreditation process even miss scoring. Due to the purpose of the research, to solve suchproblems, the writer has analyzed current system. The research object focuses on the accreditation proposing currentsystem, the scope as well as system development life cycle. The purpose of this research is to analyze problemshappened at current system as well as designing web base information system for accreditation administration. Theresult of the research is hoped to be able to solve current problems so that accreditation proposals can be processedby online system